2001
DOI: 10.1007/pl00003986
|View full text |Cite
|
Sign up to set email alerts
|

Sample size and the Binomial CUSUM Control Chart: the case of 100% inspection

Abstract: The Binomial CUSUM is used to monitor the fraction defective p of a repetitive process, particularly for detecting small to moderate shifts. The number of defectives from each sample is used to update the monitoring CUSUM. When 100% inspection is in progress, the question arises as to how many sequential observations should be grouped together in forming successive samples. The tabular form of the CUSUM has three parameters: the sample size n, the reference value k, and the decision interval h, and these param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 13 publications
0
23
0
3
Order By: Relevance
“…Another alternative is to transform the binomial or Poisson variable to normality [17]. Finally, it is possible to use a binomial or Poisson cusum chart [18,19]. Binomial and Poisson cusum charts are designed for the case where the underlying probability (p), or mean intensity ( ) is constant (and the purpose is to detect a sudden shift to values greater than p or ).…”
Section: Cumulative Sum Methods and Monitoring For A Single Regionmentioning
confidence: 99%
“…Another alternative is to transform the binomial or Poisson variable to normality [17]. Finally, it is possible to use a binomial or Poisson cusum chart [18,19]. Binomial and Poisson cusum charts are designed for the case where the underlying probability (p), or mean intensity ( ) is constant (and the purpose is to detect a sudden shift to values greater than p or ).…”
Section: Cumulative Sum Methods and Monitoring For A Single Regionmentioning
confidence: 99%
“…We consider binomial and poisson models. For the binomial distribution the CUSUM reference values are (Gan, 1993;Bourke, 2001):…”
Section: Discussionmentioning
confidence: 99%
“…Two reasons that this is reasonable are that: (i) in most of the situations that we have encountered the time over which samples are taken is a small fraction of the production process so there is only a small probability that a level shift will occur during a sample; and (ii) even if a shift occurs within a sample it can only have a small effect on the ARL because the only change in distribution is caused by the change in probability of a nonzero observation in the part of the sample taken before the shift. Situations where a shift occurring within a sample can have a larger effect have been considered by Reynolds and Stoumbos (2000) and by Bourke (2001).…”
Section: Recommended Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Research on CUSUM charts for monitoring fraction non-conforming can be found in Reynolds & Stoumbos (1999, 2000, Gan (1993) and Bourke (1991Bourke ( , 2001. Although these charts were not specifically developed for high yield process monitoring, they can be modified for this purpose.…”
Section: Review Of Control Charts For High Yield Processesmentioning
confidence: 99%